Adverse effect of cylindrospermopsin on embryonic development in zebrafish (Danio rerio). (February 2020) - Wang, Linping; Wang, Qilong; Xiao, Guosheng; Chen, Guoliang; Han, Lin; Hu, Tingzhang
Abstract: Eutrophication of freshwater bodies increases the occurrence of toxic cyanobacterial blooms. The cyanobacterial toxin cylindrospermopsin (CYN) is receiving great interest due to its increasing presence in waterbodies. However, the toxic effects of CYN on zebrafish development are poorly understood, especially the toxicological mechanism, which is still unclear. In this study, we examined the adverse effects of CYN on embryonic development in zebrafish. CYN (2–2000 nM) exposure decreased embryos survival rate, hatching rate, body length and eye size in a concentration-dependent manner and caused abnormalities in embryo morphology, including pericardial edema, spinal curvature, tail deformity, uninflated swim bladder, cardiac and vascular defects. CYN at concentrations of 20 nM or higher significantly increased ROS level and promoted cell apoptosis in zebrafish embryos. To preliminarily elucidate the potential mechanism of zebrafish developmental toxicity caused by CYN, we examined the expression of oxidative stress- and apoptotic-related genes. CYN could promote the expression of oxidative stress-related genes ( SOD1, CAT and GPx1 ) and induce changes in transcriptional levels of apoptotic-related genes ( p53, Bax and Bcl-2 ). Taken together, CYN induced adverse effects on zebrafish embryos development, which may associate with oxidative stress and apoptosis. These outcomes will advance our understanding of CYN toxicity, environmental problems and health hazards caused by climate changes and eutrophication. Graphical abstract: Image 1 Highlights: CYN induced developmental toxicity in zebrafish embryos. CYN induced cardiac and vascular defects during embryos development. CYN triggered oxidative stress through the changes of ROS and antioxidant genes. P53-dependent apoptotic pathway contribute greatly to CYN-induced apoptosis.